Triathlete`s preferences for adding strength training to triathlon training programming - Deugan, B. (Concordia University, 2025)
This dissertation examined triathletes` preferences and behaviors related to strength training integration within triathlon training programs, and despite growing evidence supporting the benefits of resistance training for injury prevention and performance enhancement, many endurance athletes remain hesitant to adopt strength training. The purpose of this study was to expand the current understanding of how age, gender, and experience influence strength training decisions and to translate those insights into practical strategies for coaching and athletic programming. A total of 210 triathletes completed an online survey assessing training behaviors, preferred strength modalities, session frequency, and load estimation methods. Quantitative data were analyzed using chi-square tests, Mann-Whitney U tests, and ordinal logistic regression.